Legal education in Malaysia: paradigm shift in the era of fourth industrial revolution (IR4.0) - Amirnuddin, Puteri Sofia; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
Accordingly, it is imperative for Higher Education Providers to consider the future of the legal education whether remaining status quo would be sufficient for the future law graduates or whether a transformation in the legal education is needed in order to ride along the waves of the IR4.0 and stay relevant to the industry. The ensuing discussion in the following discourses proposes a well-designed online legal education model that would be practical and functional for any university, college and any other higher learning institute in transforming legal education to be in line with in the IR4.0.